HIMALAYAN CU–MO–AU MINERALIZATION IN THE EASTERN INDO–ASIAN COLLISION ZONE: CONSTRAINTS FROM RE–OS DATING OF MOLYBDENITE - Hou Z.; Zeng P.; Gao Y.; Du A.; Fu D. (My University, 2006)
We present new Re–Os molybdenite age data on three porphyry Cu–Mo–Au deposits (Yulong, Machangqing, and Xifanping). These deposits are associated with the Himalayan adakitic magmatism that occurred in a continental collision environment, controlled by large-scale Cenozoic strike-slip faults in the eastern Indo–Asian collision zone. Three distinct episodes of Cu–Mo–Au mineralization are recognized. At Yulong, Re–Os isotopic data of four molybdenite samples from sulfide-quartz veins in the quartz–sericite alteration zone yield an isochron with an age of 40.1±1.8 Ma (2σ), coincident to a zircon sensitive high-mass resolution ion microprobe (SHRIMP) age of 40.9±0.1 Ma for the host monzogranite. The molybdenite Re–Os dates, together with K–Ar, Rb–Sr, U–Pb, and 40Ar/39Ar dates on the pre- and intra-ore porphyries, suggest that Cu–Mo–Au mineralization formed during the late stage (~40 Ma) of regional porphyry magmatism, but hydrothermal activity probably lasted to at least ~36 Ma. At Machangqing, molybdenite Re–Os data from the K–silicate and quartz–sericite alteration zones yield an isochron with an age of 35.8±1.6 Ma (2σ), which is identical to the zircon SHRIMP and bulk-rock Rb–Sr ages (35~36 Ma) of the host granite, but older than bulk-rock K–Ar dates (31~32 Ma) for associated Au-bearing quartz syenite with advanced argillic alteration. At Xifanping, five molybdenite samples from the K–silicate alteration zone yield the youngest Re–Os isochron age in the area, at 32.1±1.6 Ma (2σ). The Re–Os molybdenite dates here are younger than K–Ar ages (33.5~34.6) for hydrothermal biotite and actinolite. There is a positive correlation between the absolute age of the deposits and their Cu and Au reserves in the eastern Indo–Asian collisional zone. Episodic stress relaxation probably caused multiple magmatic intrusions, which most likely resulted in three episodes of Cu–Mo–Au mineralization in the eastern Indo–Asian collision zone.
Keywords: RE-OS ISOTOPES; PORPHYRY CU-MO-AU DEPOSITS; EASTERN INDO-ASIAN COLLISION ZONE; HIMALAYAN; TIBET